A DFT study on the complex formation between desferrithiocin and metal ions (Mg2+, Al3+, Ca2+, Mn2+, Fe3+, Co2+, Ni2+, Cu2+, Zn2+). (April 2017) - Kaviani, Sadegh; Izadyar, Mohammad; Housaindokht, Mohammad Reza
Graphical abstract: Highlights: A theoretical study on the structures of desferrithiocin with metal ions was carried out. Metal ion effect on the binding energies and stability constants have been investigated. There is a reverse correlation between the stabilization energy and the effective nuclear charge. Linear correlation between the electronic chemical hardness and stability constant was obtained. Abstract: In recent years, Metal-chelating compounds, namely siderphores have been considered very much because of their crucial role in various fields of the environmental researches. Their importance lies in the fact that they are able to be bonded to a variety of metals in addition to iron. A theoretical study on the structures of desferrithiocin siderphore coordinated to Mg 2+, Al 3+, Ca 2+, Mn 2+, Fe 3+, Co 2+, Ni 2+, Cu 2+ and Zn 2+ metal ions was carried out, using the CAM-B3LYP/6-31G(d) level of the theory in the water. In order to understand the factors which control the stability, reactivity and the strength of toxic metals excretion as well as microbial uptake of the metal-siderphore complexes, we examined the stability and binding energies of the desferrithiocin and various metal ions with different spin states. The binding affinity of desferrithiocin to Fe 3+ (log β2 = 23.88) showed that the desferrithiocin can scavenge the excess iron(III) from the labile sources. Also, the binding energy values were well described by addition of the dispersion-corrected D3 functional. Because of the importance of the charge transfer in the complex formation, donor-acceptor interaction energies were evaluated. Based on this analysis, an increase in the effective nuclear charge increases E(2) values. Vibrational analysis showed that the critical bonds (CO stretching and CH bending) are in the range of 1300–1800 cm −1 . Finally, some probable correlations between the complexation behavior and quantum chemistry descriptors have been analyzed.